Effects of Genotype, Storage Temperature and Time on Quality and Compositional Traits of Cherry Tomato - Distefano, Miriam (Foods, 2020)
The experiment addressed the effects of two storage temperatures, namely 10 (T(10)) and 20 °C (T(20)), on main quality and functional traits of three cherry tomato cultivars (‘Eletta’, ‘Sugarland’ and ‘Ottymo’), after 0 (S(0)), 7 (S(7)) and 14 (S(14)) days of storage. At T(10) both fruit weight and firmness were better retained during storage. At S(14), T(10) promoted fruit Chroma and overall fruit color deviation (ΔE*(ab)). Total polyphenols content (TPC) of fruits peaked at S(7) (4660 mg GAE kg(−1) DW) then declined at S(14) (by 16%), with the highest values recorded at T(10). Lycopene showed a similar trend, but with a higher average concentration recorded at T(20) (488 mg kg(−1) DW). β-carotene content peaked at S(14), irrespective of the storage temperature. At S(14), the concentrations of phytoene and phytofluene were higher at T(20) (48.3 and 40.9 mg kg(−1) DW, respectively), but the opposite was found at S(7). ‘Sugarland’ and ‘Ottymo’ showed the highest ΔE*(ab) along storage, with the former cultivar proving the highest TPC and lycopene content, whereas ‘Eletta’ did so for phytoene and phytofluene. Our results suggest that unravelling the possible functional interactions among these three carotenoids would allow for a better orientation of breeding programs, targeting the phytochemical evolution of tomatoes during refrigerated storage.